OPTIMIZATION OF THE UTILIZATION OF PASURUAN REGENCY GOVERNMENT SOCIAL MEDIA IN POLICY COMMUNICATION AND REGIONAL PROMOTION - Ardyan Setyo Prabowo (PT. Radja Intercontinental Publishing, 2026)
The quick growth of information and communication technology has equally brought about changes in the process of communication within the governance system. In this case, the utilization of social media becomes very important because it can be used to disseminate information and boost the region. Nevertheless, the application of social media in the local government is mostly done during ceremonies rather than for communicating policies. This research focuses on identifying the utilization of social media in policy communication and regional promotion of the Pasuruan Government, as well as the necessity to implement a social media governance policy. This study used a qualitative policy analysis method, including such techniques as document analysis, social media monitoring, and secondary data analysis. Information was assessed using descriptive analytical approach to uncover communication tendencies, institutional problems, social media governance needs, and policy recommendations concerning the management of social media by the local government. Furthermore, this research utilized the USG (Urgency, Seriousness, Growth) technique to define priorities and the Dunn policy analysis framework to assess alternative policies. According to the findings, although government social media accounts show relatively high levels of audience reach, engagement and effectiveness of policy communication remain low. Existing content is still primarily related to the documentation of ceremonial events. Interaction between government institutions and the general population remains insufficient and inconsistent. Also, the lack of an integrated governance approach, communication guidelines, key performance indicators, and coordination mechanisms has led to social media management by local government to be fragmented and ineffective. This study concluded that optimization of social media activities by governmental organization requires an implementation of integrated social media governance policy, which would regulate communication guidelines, public interaction, coordination and assessment of performance. As a result, this study recommended adopting an integrated social media governance policy in the Government of Pasuruan Regency.